2022
DOI: 10.1002/smll.202200915
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Triggered Size‐Tunable Silver Nanoparticles: Targeted Aggregation for Effective Bacterial Infection Therapy

Abstract: The rapid spread of drug‐resistant pathogens threatens human health. To address the current antibacterial dilemma, the development of antibiotic‐free strategies using nanotechnology is imperative. In this study, silver nanoparticles (Ag‐P&C NPs) with pH‐sensitive charge reversal and self‐aggregation capacities are successfully synthesized. In the acidic microenvironment of bacterial biofilms, protonation of the surface peptide enhances the affinity of Ag‐P&C NPs for bacteria, which can make Ag‐P&C NPs prone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 52 publications
1
55
0
Order By: Relevance
“…Silver NPs (AgNPs) attach to cell membrane, interact with membrane proteins, increase membrane porosity, enter and enhance generation of reactive oxygen species (ROS) hampering respiration, including bacterial cell lysis, and evoking inflammatory reactions [69]. A recent study shows that the pH-triggered aggregation of AgNPs favors their penetration into bacterial biofilms [70]. The large aggregated AgNPs remain in the biofilms for a long time, disrupt bacterial biofilm formation, and exhibit better antibacterial activity than traditional AgNPs [70].…”
Section: Nanoscale Antimicrobial Substancesmentioning
confidence: 99%
See 3 more Smart Citations
“…Silver NPs (AgNPs) attach to cell membrane, interact with membrane proteins, increase membrane porosity, enter and enhance generation of reactive oxygen species (ROS) hampering respiration, including bacterial cell lysis, and evoking inflammatory reactions [69]. A recent study shows that the pH-triggered aggregation of AgNPs favors their penetration into bacterial biofilms [70]. The large aggregated AgNPs remain in the biofilms for a long time, disrupt bacterial biofilm formation, and exhibit better antibacterial activity than traditional AgNPs [70].…”
Section: Nanoscale Antimicrobial Substancesmentioning
confidence: 99%
“…A recent study shows that the pH-triggered aggregation of AgNPs favors their penetration into bacterial biofilms [70]. The large aggregated AgNPs remain in the biofilms for a long time, disrupt bacterial biofilm formation, and exhibit better antibacterial activity than traditional AgNPs [70]. Gold NPs (AuNPs) exert bactericidal effects by accumulating on the cell surface credited to heavy electrostatic forces accompanied by cytoplasmic leakage and cell death [71].…”
Section: Nanoscale Antimicrobial Substancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal elements exhibit excellent antibacterial and anti-oxidative stress effects ( Makvandi et al, 2020 ), thereby facilitating synergistic anti-bone infection and osteoarthritis effects to the delivered components ( Luo et al, 2021 ); however, a few other metal elements can also endow nano-delivery systems with special targeted delivery ( Niculescu and Grumezescu, 2022 ), photodynamic therapy (PDT) ( He et al, 2022 ), thermodynamic therapy ( Boroushaki et al, 2022 ), bioimaging ( Zhong et al, 2021 ), and stimuli-responsive ( Hu et al, 2022 ) functions, which are more conducive to the efficient diagnosis and treatment of bone diseases or promote bone regeneration, and decrease the simple systemic side effects of drug use. A few of researchers reported that metal nanoparticles (NPs) can be used as nano-antibiotics because of their favorable antibacterial activities and significant potential to combat antibiotic resistance ( Cheng et al, 2022 ). In addition, studies have demonstrated that metal-based nanomaterials possess excellent mechanical properties as well as the intrinsic ability to significantly promote osseointegration, osteoconductivity, and osteoinduction, which has become crucial factors for bone regeneration ( Sobolev et al, 2019 ; Eivazzadeh-Keihan et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%